A biological guided missile - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Biological warfare in the soil is being encouraged through a product containing parasitic nematodes for the control of damaging soil pests such as weevils